Lyme disease presenting as multiple ischaemic strokes. Issue 4 (16th April 2015) - Li, Sui; Vytopil, Michal; Hreib, Kinan; Craven, Donald E
Abstract : A 46-year-old man presented with recurrent left hemiparesis and headache. MRI of brain showed an acute right pontine and subacute right thalamic infarcts and MR angiogram showed multiple intracranial arterial stenoses, suggesting cerebral vasculopathy. There was a cerebrospinal fluid lymphocytic pleocytosis with Borrelia burgdorferi antibodies. Central nervous system Lyme disease occasionally presents with ischaemic strokes; this case is unusual in showing vasculopathy on brain imaging, supporting meningovasculitis as the likely mechanism.